Spin Seebeck effect and ballistic transport of quasi-acoustic magnons in room-temperature yttrium iron garnet films. (17th May 2018) - Noack, Timo B; Musiienko-Shmarova, Halyna Yu; Langner, Thomas; Heussner, Frank; Lauer, Viktor; Heinz, Björn; Bozhko, Dmytro A; Vasyuchka, Vitaliy I; Pomyalov, Anna; L'vov, Victor S; Hillebrands, Burkard; Serga, Alexander A
Abstract: We studied the transient behavior of the spin current generated by the longitudinal spin Seebeck effect (LSSE) in a set of platinum-coated yttrium iron garnet (YIG) films of different thicknesses. The LSSE was induced by means of pulsed microwave heating of the Pt layer and the spin currents were measured electrically using the inverse spin Hall effect in the same layer. We demonstrate that the time evolution of the LSSE is determined by the evolution of the thermal gradient triggering the flux of thermal magnons in the vicinity of the YIG/Pt interface. These magnons move ballistically within the YIG film with a constant group velocity, while their number decays exponentially within an effective propagation length. The ballistic flight of the magnons with energies above 20 K is a result of their almost linear dispersion law, similar to that of acoustic phonons. By fitting the time-dependent LSSE signal for different film thicknesses varying by almost an order of magnitude, we found that the effective propagation length is practically independent of the YIG film thickness. We consider this fact as strong support of a ballistic transport scenario—the ballistic propagation of quasi-acoustic magnons in room temperature YIG.